y'' = +λ*y Verify that cosh( λt - 4) is a solution to our ODE. Express this function in terms of both our old exponential basis, and our new hyperbolic basis.
Follow Math Help Forum on Facebook and Google+
Originally Posted by thehollow89 y'' = +λ*y Verify that cosh( λt - 4) is a solution to our ODE. Express this function in terms of both our old exponential basis, and our new hyperbolic basis. 1)To show this is a solution just substitute. 2)To express in hyperbolic basis use . 3)Once expressed in hyperbolic basis replace by exponentials.
View Tag Cloud